Use of textile waste as an addition in the elaboration of an ecological concrete block - Anglade, J. (2021)
The textile industry has grown significantly in recent years, reaching a global fiber production of 53 million tons which 12 % are recycled; Construction sector has been using more and more recycled materials from different industrial sources, to apply them in their constructions and to reduce CO2 emissions and final energy consumption. The present study aims to study the behavior of concrete blocks of fć= 210 kg/cm2 adding polyester textile waste with 3 %, 6 %, 9 %, 12 % and 15 %; void content, compressive strength and thermal conductivity decrease, and water absorption, acoustic insulation and unit price increase by 3 %, 34 % and 16 % compared to conventional concrete block.